Pertumbuhan dan Hasil Kentang G1 Melalui Modifikasi Media Tanam dan Aplikasi Zat Pengatur Tumbuh - Suliansyah, Irfan; Hervani, Dini; Sari, Silvia Permata; Muhsanati, Muhsanati; Ekawati, Fitri Ekawati, (Jurnal Agroekoteknologi, 2023)
Success in cultivating potatoes is the use of good quality potato seeds. Good quality potato seeds are produced through several stages starting from in vitro culture to extension seed production. One of the important stages in potato seed production is the production of first generation (G1) potato seeds. Efforts to increase the yield of G1 tubers can be made through modifying the planting media and applying growth regulators. This research aims to produce G1 potato tubers by adjusting the composition of the planting media (cocopeat, cocofiber, charcoal husk) and applying a growth inhibitor (Daminozide). The research consisted of four series of experiments. Each experiment was carried out using a Completely Randomized Design (CRD) with six treatments, each repeated four times. Experiment 1 (a. Cocopeat 100% + 0% husk charcoal; b. Cocopeat 20% + 80% husk charcoal; c. Cocopeat 40% + 60% husk charcoal; d. Cocopeat 60% + 40% husk charcoal; e. Cocopeat 80% + Charcoal Husk 20%; f. Cocopeat 0% + Charcoal Husk 100%. Experiment 2 (a. Cocofiber 100%; b. Cocopeat 100%; c. Cocopeat 20% + Cocofiber 80%; d. Cocopeat 40% + Cocofiber 60%; e. Cocopeat 60% + Cocofiber 40%; f. Cocopeat 80% + Cocofiber 20%. Experiment 3 (a. Cocopeat + Cocofiber + husk charcoal (1 : 1 : 1); b. Cocopeat + Cocofiber + charcoal husk (1 : 1 : 2); c. Cocopeat + Cocofiber + husk charcoal (1 : 2 : 1); d. Cocopeat + Cocofiber + husk charcoal (2 : 1 : 1). Experiment 4 (a. Daminozide 0 ppm; b. Daminozide 500 ppm; c. Daminozide 1000 ppm; d. Daminozide 1500 ppm). From the research results it can be concluded: 1) The combination treatment of 80% cocopeat + 20% cocofiber is the best treatment combination in the vegetative growth phase; 2) Composition treatment 60% cocopeat + 40% husk charcoal is the best treatment for the growth and number of G1 potato tubers; 3) Treatment of the composition of the planting media with cocopeat, cocofiber, and husk charcoal with a composition of 1:1:1 produces the highest number of tubers; 4) The best concentration of daminozide for the growth and production of G1 potato seed tubers is 3500 ppm.